Combination CBD/THC in the management of chemotherapy-induced peripheral neuropathy: a randomized double blind controlled trial - Weiss, Marisa; Giaddui, Muath; Kjelstrom, Stephanie; Gary, Joseph; Ward, Sara Jane; Burrell, Jessica; Diguilio, Katherine; Bidas, Gabrielle; Erebor, Ebuwa; Meske, Sam; Saeed, Lisa; Windawi, Sarah; et al. (Frontiers in Oncology, 2025)
IntroductionChemotherapy-induced peripheral neuropathy (CIPN) can greatly impair function, leading to disability or truncated treatment in cancer patients. Previous animal studies show that cannabidiol (CBD) and delta-9- tetrahydrocannabinol (THC) can ameliorate CIPN. This study assessed the effect of combined CBD and THC on CIPN symptoms amongst cancer patients treated with taxane- or platinum-based agents.Materials and methodsThis 12-week randomized, double-blind, placebo-controlled trial included participants with nonmetastatic breast, colorectal, endometrial, or ovarian cancer experiencing grade 2–3 CIPN. The active group received CBD (125.3-135.9 mg) combined with THC (6.0-10.8 mg) in gelcaps. The Quality-of-Life Questionnaire-CIPN twenty-item scale (QLQ-CIPN20) sensory subscale was used as the primary outcome. Additional outcomes assessed pain, sleep, and function. Neurologic exams evaluated touch, pressure, and vibration sense. Following the randomized controlled trial, participants were invited to enroll in a 12-week open-label observational study.ResultsOf 230 participants identified, 124 met eligibility, 54 were enrolled, 46 were randomized, and 43 completed 12 weeks of treatment. This was lower than our goal of 100 randomized participants. The mean age was 60 +/- 9 years, 88% were female, 63% had breast cancer. All participants had completed chemotherapy. The primary analysis showed no differences in outcome measures between active and placebo groups, likely due to sample size. Although an increase in bilirubin (one participant in active group, and one in placebo) and alkaline phosphatase (one participant in active group) was seen, this did not exceed the exit criteria. A secondary analysis showed that the active group experienced greater improvement in the QLQ-CIPN20 measures of sensory impairment relative to placebo (-10.4 (95% -20.5, -0.3), p = 0.044). There was also improvement in light touch and vibration sensation of the feet on neurological exam that approached significance. There was no effect on other measures, including pain, and no between-group differences in side effects. The uncontrolled observational study showed similar results.DiscussionThe primary analysis showed no between-group difference in CIPN symptoms. The secondary analysis indicated that CBD with THC could improve sensory impairment and might increase touch and vibration sense, although these findings require confirmation in a future, more fully powered study. Nonetheless, our results show that combination CBD/THC can be safely delivered to participants with CIPN and suggest that these cannabinoids should be further investigated for this indication.